(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
In this article we can see these aim of our study was to study the features of the correction of metabolic disorders in women of the perimenopausal period. The menopausal transition is a special period in the life of women, which requires increased attention to health [1,8,9].